Characteristics of Quinolone Resistance in Salmonella spp. Isolates from the Food Chain in Brazil - Pribul, Bruno R.; Festivo, Marcia L.; Rodrigues, Marcelle S.; Costa, Renata G.; Rodrigues, Elizabeth C. dos P.; de Souza, Miliane M. S.; Rodrigues, Dalia dos P. (Frontiers in Microbiology, 2017)
Salmonella spp. is an important zoonotic pathogen related to foodborne diseases. Despite that quinolones/fluoroquinolones are considered a relevant therapeutic strategy against resistant isolates, the increase in antimicrobial resistance is an additional difficulty in controlling bacterial infections caused by Salmonella spp. Thus, the acquisition of resistance to quinolones in Salmonella spp. is worrisome to the scientific community along with the possibility of transmission of resistance through plasmids. This study investigated the prevalence of plasmid-mediated quinolone resistance (PMQR) in Salmonella spp. and its association with fluoroquinolone susceptibility in Brazil. We evaluated 129 isolates, 39 originated from food of animal sources, and 14 from environmental samples and including 9 from animals and 67 from humans, which were referred to the National Reference Laboratory of Enteric Diseases (NRLEB/IOC/RJ) between 2009 and 2013. These samples showed a profile of resistance for the tested quinolones/fluoroquinolones. A total of 33 serotypes were identified; S. Typhimurium (63) was the most prevalent followed by S. Enteritidis (25). The disk diffusion test showed 48.8% resistance to enrofloxacin, 42.6% to ciprofloxacin, 39.53% to ofloxacin, and 30.2% to levofloxacin. According to the broth microdilution test, the resistance percentages were: 96.1% to nalidixic acid, 64.3% to enrofloxacin, 56.6% to ciprofloxacin, 34.1% to ofloxacin, and 30.2% to levofloxacin. Qnr genes were found in 15 isolates (8 qnrS, 6 qnrB, and 1 qnrD), and the aac(6′)-Ib gene in 23. The integron gene was detected in 67 isolates with the variable region between ±600 and 1000 bp. The increased detection of PMQR in Salmonella spp. is a serious problem in Public Health and must constantly be monitored. Pulsed-field gel electrophoresis was performed to evaluated clonal profile among the most prevalent serovars resistant to different classes of quinolones. A total of 33 pulsotypes of S. Typhimurium were identified with a low percentage of genetic similarity (≤65%). This result demonstrates the presence of high diversity in the resistant clones evaluated in this study.